Bacterial adhesion on lithium disilicate ceramic surface exposed to different hydrofluoric solutions - Dos Santos, Daniela Micheline [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Matos, Adaias Oliveira; Monteiro, Beatriz Cristiane Zuin [UNESP]; de Medeiros, Rodrigo Antonio; Bitencourt, Sandro Basso [UNESP]; Barão, Valentim Adelino Ricardo; Rangel, Elidiane Cipriano [UNESP]; Goiato, Marcelo Coelho [UNESP] (MDPI, 2018)
The effect of Fluorine solutions on the surface and bacterial adhesion of lithium disilicate is a concern. The aim was to evaluate the surface roughness and the adhesion of Streptococcus sanguinis on lithium disilicate ceramic, under the influence of different solutions containing Fluorine. Forty lithium disilicate (IPS e.max Press Impulse) discs (2.5 × 5 mm) was divided into 4 groups (n = 10): artificial saliva (Group AS), 0.2% sodium fluoride (Group NaF), 1.23% acidulated phosphate fluoride gel (Group APF), and mouthwash (Group MW). Roughness analyses were performed before and after the immersion. The surface aspect was evaluated by scanning electron microscopy (SEM) and the adhesion of Streptococcus sanguinis were evaluated after immersion in the solutions. The data obtained were submitted to the analysis of variance (ANOVA) and the Tukey test (α = 0.05). The Group APF presented a bigger roughness (3.263), statistically different to the other solutions. The bacterial adhesion in the Group APF (5.85) presented statistical difference to the other solutions. The SEM micrographs showed a rougher surface in Group APF. The 1.23% APF gel promoted major surface roughness and bacterial adhesion and could be inadequate for the use of patients with lithium disilicate ceramic restorations. Clinical significance: The Fluorine solution can affect the lithium disilicate ceramics, generating a rough and non-esthetic surface. This altered surface could be susceptible to bacterial adhesion, being directly related with periodontal health, the longevity of the restoration and the success of the rehabilitation.
Keywords: Acidulated Phosphate Fluoride; Bacterial adhesion; Biofilms; Ceramics; Fluoride